Controlled decoration of palladium (Pd) nanoparticles on graphene nanosheets and its superior field emission behavior. (August 2021) - Dusane, Pravin R.; Gavhane, Dnyaneshwar S.; Kolhe, Pankaj S.; Bankar, Prashant K.; Thombare, Balu R.; Lole, Gaurav S.; Kale, Bharat B.; More, Mahendra A.; Patil, Shankar I.
Graphical abstract: Highlights: Pd NPs decorated graphene with different wt % of Pd NPs were synthesized by chemical method. Pd NPs binds strongly on graphene surface inducing local structural deformations thus altering the FE behavior of Pd-Gr emitters. FN plot for Gr, Pd1-Gr and Pd4-Gr is linear, indicating metallic nature of emitters. FN plot for Pd2-Gr and Pd3-Gr it deviates slightly from linearity thereby indicating semiconducting behavior. Maximum current density and minimum turn on and threshold field was observed for Pd3-Gr. Abstract: Development in nanoscience and nanotechnology has inspired scientists to continuously explore new cathode material for field emission applications. In the present article, different weight (wt) % of Pd nanoparticles (Pd NPs) ensemble on graphene (Gr) nanosheets (Pd-Gr) were prepared via one step simple chemical route. The field emission (FE) properties of Pd decorated Gr nanosheets were studied. Structural and morphological analysis of as synthesized Pd-Gr composites were carried out by using X-ray diffraction (XRD), Raman spectroscopy and t ransmission electron microscope (TEM). The FE properties of the Pd-Gr changed according to the variation in the wt% of Pd NPs. The Pd3-Gr field emitter showed better performance among all the emitters with lower turn on field, threshold field and maximum emission current density ( J ). The enhanced FE properties of Pd-Gr are due to the decoration of low work function Pd NPs. The FE results demonstrated herein suggest that, Pd-Gr based field emitters can open up many opportunities for their potential utilization in large area field emitters in various vacuum micro-nanoelectronic devices such as flexible field emission displays, portable X-ray and microwave tubes.